Sinergi Program KKN dan Pancasila dalam Membangun Desa Rowoboni: Menyongsong Desa Penggerak Pancasila - Benedicta Keisya Ambarrini; Kevin Ariel Maghfiroh (Jurnal Bina Desa, 2026)
The Community Service Program (KKN) in Rowoboni Village aims to implement Pancasila values in the village's development towards becoming a Pancasila-Driven Village. The background of this study is the need to integrate Pancasila values into the village community's life to enhance social cohesion and economic empowerment. The focus of this service activity is on the Rowoboni Village community, with an emphasis on education, economy, and socio-cultural aspects. The methods used include training sessions, discussions, and the implementation of Pancasila-based programs. The process involves identifying the village’s needs, program planning, implementation, and impact evaluation. The results indicate that the synergy between the KKN program and Pancasila values effectively increased the community's awareness of Pancasila’s importance, strengthened social solidarity, and promoted local economic development. The program also positively contributed to reinforcing Pancasila identity in the village's daily life. These findings highlight the significance of collaboration between higher education institutions and the community in creating a competitive and harmonious village.